Importance of Primary Prevention for Arterial Hypertension and Cardiovascular Risks (Global Journal of Medical Research, 2015)
Summary Arterial hypertension is a mass, non contagious disease influenced by numerous risk factors and itself presents a risk factor for cardiovascular and cerebra vascular disease, kidney disease and peripheral blood vessel disease. (1) Therefore, primary prevention today contains cardiovascular risk assessment, based on SCORE (Systematic Coronary Risk Eva luation) charts which are used to assess ten years risk for initial (first) fatal arteriosclerotic event. Our research covered 39 subjects with arterial hypertension, both genders, aged between 40 and 54, who were motivated for decisive implementation of p rimary prevention measures in accordance with recommendations for cardiovascular diseases prevention and which are promoting healthy life style.
Keywords: primary prevention; arterial hypertension; cardiovascular risk; score